2006
DOI: 10.1093/hmg/ddl038
|View full text |Cite
|
Sign up to set email alerts
|

Correction of Hunter syndrome in the MPSII mouse model by AAV2/8-mediated gene delivery

Abstract: Mucopolysaccharidosis type II (MPSII; Hunter syndrome) is a lysosomal storage disorder caused by a deficiency in the enzyme iduronate 2-sulfatase (IDS). At present, the therapeutic approaches for MPSII are enzyme replacement therapy and bone marrow transplantation, although these therapies have some limitations. The availability of new AAV serotypes that display tissue-specific tropism and promote sustained expression of transgenes offers the possibility of AAV-mediated gene therapy for the systemic treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
90
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(96 citation statements)
references
References 18 publications
4
90
1
1
Order By: Relevance
“…Following i.v. administration of 4 × 10 12 vg/kg of recombinant AAV8-TBG-IDS vector to adult MPSII mice, plasma concentrations of IDS were 16-to 70-fold higher than in WT, and complete correction of somatic disease was achieved (61). However, efficacy in the brain was limited, with only partial reduction of GAGs observed in this organ, likely due to the fractional amount of IDS that crossed the BBB despite the high concentration of circulating enzyme.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Following i.v. administration of 4 × 10 12 vg/kg of recombinant AAV8-TBG-IDS vector to adult MPSII mice, plasma concentrations of IDS were 16-to 70-fold higher than in WT, and complete correction of somatic disease was achieved (61). However, efficacy in the brain was limited, with only partial reduction of GAGs observed in this organ, likely due to the fractional amount of IDS that crossed the BBB despite the high concentration of circulating enzyme.…”
Section: Discussionmentioning
confidence: 97%
“…Here, we report CNS-directed gene therapy developed for the treatment of the severe phenotype of MPSII and provide evidence of the therapeutic efficacy of the approach to treat not only neurologic but also somatic pathology in animals with already established disease. Previous attempts to treat neurologic MPSII with AAV tested systemic vector delivery to achieve supraphysiological concentrations of circulating IDS (60,61). This strategy was based on earlier work with ERT for different forms of LSD that suggested that when high levels of enzyme are present in the bloodstream, a portion of the protein manages to cross the BBB (62, 63).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] However, despite long-term efficacy data in experimental animals, in the only human study of AAV-mediated, liver-directed gene transfer, expression of the donated F.IX gene was short-term in hemophilic men, 10 persisting for approximately 4 weeks, then gradually declining over the ensuing 6 weeks. Loss of F.IX expression was accompanied by a transient asymptomatic transaminase elevation, also beginning 4 weeks after vector infusion.…”
Section: Introductionmentioning
confidence: 99%
“…The AAV2/8 serotype transduces hepatocytes with high efficiency and the TBG promoter is liver specific; therefore, SUMF1 can only be expressed by the liver (Cardone et al, 2006). We transduced 2-month-old wildtype mice (n ¼ 3) by tail-vein injection with a total of 2.8 Â10 11 viral particles.…”
Section: Sumf1 Is Secreted and Taken Up In Vivomentioning
confidence: 99%